(3eYjGQ GdQDjG HGdbQBfs - (3Ydj Hf SYjO GdNhdGfj GdbUGQ, CHh GdMSfs ((3CMeO Hf EHQGgje Hf eSYhO s)
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdcHjQ GddWja GdNHjQ CYde QMec Gddg Cf GdQDjG GdUGdMI HTGQI dCeI eMeO Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3dbhdg JYGdi (B:" (3SHY djGd hKeGfjI CjGe (B" (3hSdGe Ydi YHGOg GdPjf EUWai s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(505 d) s
Keywords: (3GdeLGejYs